Strategiczni inwestorzy zagraniczni w polskich spółkach giełdowych - motywy przejęć i sprawowania kontroli - Wypych, Mirosław (Strategic Foreign Investors in Polish Stock Enterprises - Reasons for Takeovers and Control, 2007)
Capital market is one of the directions of foreign investments in Poland, stock exchange included as its important element. Foreign investors achieve their defined targets by taking the decisions about buying enterprises' stocks. The paper assesses the scale of foreign investors' involvement in the Polish public stock companies fusions or takeovers processes and discusses their reasons for taking investments decisions. These are the long term decisions and have remarkable influence both on activity of controlled companies and all stock markets. That is why in the last part of the paper the attention has been paid to some financial consequences of international investors' activity. It has been also concluded that international investors' behaviour relates strictly to company's financial results.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1152, s. 656-663